Chemically Modified Polyaniline for the Detection of Volatile Biomarkers of Minimal Sensitivity to Humidity and Bending. Issue 15 (23rd May 2018) - Deng, Yunfeng; Sun, Jiaxing; Jin, Han; Khatib, Muhammad; Li, Xianhui; Wei, Zongsu; Wang, Feng; Horev, Yehu David; Wu, Weiwei; Haick, Hossam
Abstract: Flexible sensors can be widely used in future wearable devices to monitor people's health states. However, most of the sensors are sensitive to humidity and bending effects, limiting their application in a real‐world environment. A new strategy is proposed for obtaining flexible sensors with good tolerance to humidity. By integrating a hydrophobic layer on the surface of doped polyaniline, a flexible sensor that can resist water response with a concentration up to 350 ppm is developed. Good resilience against mechanical bending is also achieved in this flexible sensor. These results may trigger a renaissance in flexible sensor applications for disease diagnosing by wearable devices. Abstract : By integrating a hydrophobic layer on the surface of doped polyaniline, a flexible gas sensor with minimal sensitivity to humidity and mechanical bending is demonstrated. These results may trigger the renaissance of flexible gas sensor applications in wearable devices for disease diagnosis.